Physicochemical analysis of floral honeys produced by Apis mellifera L. between 2018 and 2020 in the State of Santa Catarina, southern Brazil (Revista de Ciências Agroveterinárias, 2024)
Brazil is a major producer of honey and is internationally recognized for the quality of this product. To assess the quality of the product, physicochemical analyses were carried out. In this sense, samples of honey from the eleven agroecological zones of Santa Catarina, southern Brazil, were analyzed for moisture content, pH, reducing sugars, apparent sucrose, water activity, diastase enzyme, color, and Lund reaction. Sixty-five samples of honey collected in the 2018-2019 harvest and 50 in the 2019-2020 harvest were analyzed. The data were analyzed using analysis of variance and the Scott & Knott test (p
Keywords: Beekeeping; PCA; Food safety